Diet-Derived Antioxidants and Risk of Kidney Stone Disease: Results From the NHANES 2007–2018 and Mendelian Randomization Study - Jian, Zhongyu; Wang, Menghua; Jin, Xi; Li, Hong; Wang, Kunjie (Frontiers in Nutrition, 2021)
We aimed to explore the associations between diet-derived antioxidants and kidney stone disease (KSD) risk in this study. We performed weighted multivariable-adjusted logistic regression to assess the associations between six main diet-derived antioxidants and the risk of KSD using data from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. Then, we used the Mendelian randomization (MR) approach to verify the causal relationships between circulating antioxidants levels and KSD risk. Genetic tools were extracted from published genome-wide association studies (GWAS). Summary data for KSD was from the FinnGen study and UK biobank. Inverse variance weighted (IVW) was the primary analysis. 25,806 participants including 2,475 stone formers (Weighted N = 21,075,463) were included for analyses. There were no significant associations between retinol, vitamin B6, vitamin C, vitamin E and lycopene intake with the risk of KSD across all the quartile categories. Similarly, pooled OR for KSD risk in genetically predicted per unit change were 1.25 (95%CI: 0.39, 4.02; P = 0.712), 1.14 (95%CI: 0.84, 1.53; P = 0.400), 0.75 (95%CI: 0.52, 1.10; P = 0.141), 0.93 (95%CI: 0.28, 3.06; P = 0.904), 1.27 (95%CI: 0.29, 5.62; P = 0.756), and 0.92 (95%CI: 0.76, 1.12; P = 0.417) for retinol, β-carotene, vitamin B6, vitamin C, α-tocopherol and lycopene, respectively. The above estimates were replicated in the secondary analyses using UK biobank data. Our study suggests that increasing diet-derived antioxidants intake to elevate circulating antioxidants levels is of limited clinical benefit for reducing the risk of KSD in the general population based on current evidence and should be verified in further studies.